The flowers of war - Yan, Geling 1958- (Vintage Books, 2013)
Based on true events that took place during the Nanjing Massacre in 1937 when the Japanese invaded the Chinese city, slaughtering not only soldiers but raping and murdering the civilian population as well
First published with the title Jingling Shisan Chai in 2006
Keywords: Nanking Massacre, Nanjing, Jiangsu Sheng, China, 1937 / Fiction; Americans / China / Nanjing (Jiangsu Sheng) / Fiction; Japanese fiction / China / Nanjing (Jiangsu Sheng); Women / China / Nanjing (Jiangsu Sheng) / Fiction; Comfort women / China / Fiction; Frau; Fiktionale Darstellung